Dynamic response of orthogonal 3D woven carbon composites under soft impact - Turner, Paul; Liu, Tao; Zeng, Xuesen (American Society of Mechanical Engineers, 2015)
This paper presents an experimental and numerical investigation into the dynamic response of 3D orthogonal woven carbon composites undergoing soft impact. Composite beams of two different fibre architectures, varying only by the density of through-thickness reinforcement, were centrally impacted by metallic foam projectiles. Using high speed photography, the centre-point back-face deflection was measured as a function of projectile impulse. Qualitative comparisons are made with a similar uni-directional laminate material. No visible delamination occurred in orthogonal 3D woven samples, and beam failure was caused by tensile fibre fracture at the gripped ends. This contrasts with uni-direction carbon fibre laminates, which exhibit a combination of wide-spread delamination and tensile fracture. Post-impact clamped-clamped beam bending tests were undertaken across the range of impact velocities tested in order to investigate any internal damage within the material. Increasing impact velocity caused a reduction of beam stiffness: this phenomenon was more pronounced in composites with a higher density of through-thickness reinforcement. A three-dimensional finite element modelling strategy is presented and validated, showing excellent agreement with the experiment in terms of back-face deflection and damage mechanisms. The numerical analyses confirm negligible influence from though-thickness reinforcement in regards to back-face deflection, but significant reductions in delamination damage propagation. Finite element modelling was used to demonstrate the significant structural enhancements provided by the through-the-thickness weave. The contributions to the field made by this research include the characterisation of 3D woven composite materials under high-speed soft impact, and the demonstration of how established finite element modelling methodologies can be applied to the simulation of orthogonal woven textile composite materials undergoing soft impact loading.